THE ESSENCE OF MORAL SENTIMENTS AS REGULATORY MECHANISMS IN HUMAN LIFE. - Турчин, М. Я. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article investigatesthe features of moralsentiments in theself-determination and self manifestation of personality.